THE EFFECT OF INDONESIAN SPICE EXPORT TRADE LIBERALIZATION ON COMPETITIVENESS AND COMPETITIVENESS IN INTERNATIONAL MARKETS - Herdiana Anggrasari; Dhika Cahyasita; Dinda Dewi Aisyah (JURNAL AGRIBISNIS TERPADU, 2023)
Since long time ago, Indonesia has had a comparative advantage because of its geographical advantage in spice commodities. In the era of liberalization, in order to be competitive in the same industry, Indonesian spice commodities must increase their export share by having a distinct advantage compared to competitors from other countries. Therefore, the purpose of this study is to determine the effect of Indonesia's trade liberalization based on competitiveness with competing countries and the level of competition for Indonesian spice commodities in the international market. The analytical methods used are Revealed Comparative Advantage (RCA), Export Similarity Index (ESI), and Export Overlapping Index (IEO) which are discussed descriptively using secondary data from UNComtrade for 1989-2021. Trade liberalization is indicated by Indonesia's entry into the WTO, AFTA and ACFTA. The results of the analysis show that even though Indonesia has very strong competitiveness, the existence of trade liberalization is not enough to increase Indonesia's competitiveness because the international market is increasingly open. The level of competition for Indonesian spice exports with its competitor countries tends to decrease. The existence of trade liberalization makes each country increase its trade specialization in order to expand its market share. Indonesia needs to improve quality as well as standardize and increase differentiation for spice products in order to maintain and expand its market share so that it can be competitive in the international market.